When Citizens’ Grievances Entered the Policy Agenda, 1963-1969 - Joana Etchart (Revue Française de Civilisation Britannique)
This article analyses how citizens’ grievances entered the policy agenda in the years mounting to 1969 in Northern Ireland. At that critical juncture, a disparate group composed of individuals, organisations and members of the Opposition in the Parliament of Northern Ireland were pushing for comprehensive reforms in the field of civil rights. Their efforts contributed to bringing the question of citizens’ grievances into the realm of public policy, to the extent that a robust reform package was envisaged from 1968, which then went under the heading of community relations in 1969. But the close analysis of that shift also reveals strong resistance to reforms. This was evident in the mechanism consisting in seeking to contain the policy problem within the realm of fate, by invoking change in people’s conduct rather than in public action. Not only did this deny the causal responsibility of executive and legislative authorities in the issues encountered, but it also sought to avoid taking responsibility for the policy that tried to address them. By exploring these developments, this article provides a historical explanation for the tension between comprehensive and restricted interpretations of community relations policy issues, and sheds light on the conflict that existed between the promoters of each. It contends that this was also one of the causes leading to the start of the Troubles.